Camel workhorse of the desert - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Rathore G S. 1986 Camels and their Management 225pp illustrated. Indian Rs. 38.0